2018
DOI: 10.1007/s10646-018-1944-2
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic community structure in Mediterranean edge-of-field waterbodies as explained by environmental factors and the presence of pesticide mixtures

Abstract: Studies addressing the predicted effects of pesticides in combination with abiotic and biotic factors on aquatic biota in ditches associated with typical Mediterranean agroecosystems are scarce. The current study aimed to evaluate the predicted effects of pesticides along with environmental factors and biota interactions on macroinvertebrate, zooplankton and phytoplankton community compositions in ditches adjacent to Portuguese maize and tomato crop areas. Data was analysed with the variance partitioning proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 72 publications
0
6
0
2
Order By: Relevance
“…It is likely that some of these effects on phytoplankton and bacteria communities have been caused by food web cascades. Indeed, previous research showed that even under stress from pesticide mixtures, biotic interactions played a major role in the structuring of plankton communities (Pereira et al, 2018 ). Similarly, responses to nutrient pressure by fertilizer in macroinvertebrates may also partly be caused by cascade reactions, such as the aforementioned changes in food availability.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that some of these effects on phytoplankton and bacteria communities have been caused by food web cascades. Indeed, previous research showed that even under stress from pesticide mixtures, biotic interactions played a major role in the structuring of plankton communities (Pereira et al, 2018 ). Similarly, responses to nutrient pressure by fertilizer in macroinvertebrates may also partly be caused by cascade reactions, such as the aforementioned changes in food availability.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the combined environmental and biological factors that influence plankton abundance, a multivariate statistical analysis described by Pereira et al (2018) was used to more accurately determine the potential responses of planktonic taxa to neonicotinoids beyond simple linear relationships. Any meaningful interpretations of these data, however, could not be made because of the limited spatiotemporal resolution of the samples containing synchronous measurements of plankton population sizes and neonicotinoid concentrations (i.e., 3 discrete sampling events for 10 lakes in Ramsey County during 1 yr).…”
Section: Discussionmentioning
confidence: 99%
“…Current research on IBIs mainly focuses on fish (Cooper et al, 2018), macroinvertebrates (Wahl et al, 2019), plankton (Zhang et al, 2019), and bacteria (Li et al, 2017(Li et al, , 2018. These aquatic biological community structures are important markers of water pollution and eutrophication; therefore, they are often used to evaluate the damage to and health of aquatic ecosystems (Pereira et al, 2018). Phytoplankton rapidly respond to environmental changes, and their community structure accurately reflects the short-term effects of anthropogenic and natural disturbances on aquatic ecosystems (Busseni et al, 2019).…”
Section: Introductionmentioning
confidence: 99%